PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR BEKAS PADA PT. SOLUSI INTEGRASI PRATAMA DI TANGERANG SELATAN - Irawan, Ricky; Fahlevi Almassawa, Syafieq (Journal of Research and Publication Innovation, 2024)
This research aims to determine the influence of price and service quality on the decision to purchase used motorbikes at PT. Primary Integration Solutions in South Tangerang, both partially and simultaneously. This type of research uses descriptive quantitative methods. The sampling technique uses random samples, namely using a portion of the population of 82 respondents. Data analysis techniques use data instrument tests, classical assumption tests, simple linear regression, multiple linear regression, correlation coefficient, coefficient of determination. Test the hypothesis using the t test and F test. The results of the analysis show: price partially influences purchasing decisions. This is proven by the t test, the calculated t value > t table (6,648 > 1,667), the coefficient of determination value is 35.6% and the remainder 64.4% is influenced by other factors and is strengthened by a significant value < 0.05 (0.000 < 0.05). Service Quality partially has a positive influence on Purchasing Decisions. This is proven by the t test, the value of t calculated > t table (15,507 > 1,667), the coefficient of determination is 75% and the remaining 25% is influenced by other factors and is strengthened by the value significance < 0.05 (0.000 < 0.05). The results of research on price and service quality simultaneously on purchasing decisions. This is proven by the results of the F test hypothesis test which shows that the calculated F value > F table (184.671 > 3.11), the coefficient of determination value is 82.4% and the remaining 17.6% is influenced by other factors and strengthened by a significance value < 0.05 (0.000 < 0.05). Thus it is proven that Ho is rejected and Ha is accepted.